EVALUASI PROGRAM PEMBERDAYAAN MUSTAHIK “TERNAK KAMBING ETAWA MUARA FAJAR” PADA BAZ KOTA PEKANBARU - Devi Megawati ' (PEKBIS, 2015)
Zakat does have a very important role in tackling the problem of poverty . However, the most importantis how the amil can create economic empowerment programs are effective and on target. BAZ city ofPekanbaru is the official zakat institutions initiated and confirmed Pekanbaru municipalities establishedsince 2001. In general BAZ Pekanbaru has zakat distribution programs; donation and charity programthat Prosperous Pekanbaru, Pekanbaru Smart, Healthy Pekanbaru, Pekanbaru Care and Piety.Pekanbaru Makmur program is the provision of capital for productive enterprises, have alsoempowerment program which has a companion program. Empowerment programs that include theempowerment of livestock and livestock laying ducks Etawa the focus in this study. This study is anevaluation study that aims to identify the implementation of empowerment programs mustahik Etawacattle in the field , both the process of program implementation and performance of actors , as well asperformance results Identifying livestock development programs mustahik Etawa Muara districtsRumbai dawn . Research results show that mustahik (Etawa livestock beneficiaries ) has beenselected by the City in accordance with the surveyor BAZ SOP ( standard operational procedure ) ,monitoring results to the first portion mustahik goats can breed goats were given so that the number isstill growing and mentoring is done intensively . However, in monitoring II decreased number of goatshave died from illness and some are lost stolen. This program can not be said to fail, but becauseit is not an easy process to start something new, and this requires a process and patience.Although there has been no economic impact, but in non-economic lot of benefits that havebeen obtained mustahik .Keywords : Program, evaluation, empowerment, mustahik,and zakat